The development of nursery plant and fertilizer (NPF) informational web-based system / Zairidha Atiqah Zainol Abidin - Zainol Abidin, Zairidha Atiqah (2016)
This research project IS about developing a Nursery Plant and Fertilizer (NPF) Infonnational Web-Based System for the Nursery Shah Alam Seksyen 18. The main reason why the web-based platfonn is chosen because a web-based system can be accessed by both web and mobile devices. Currently, customer must make an appointment in order to get infonnation about plant and fertilizer because in the Nursery does not have knowledgeable staff that can help owner give the infonnation. The purpose of this research is to develop a Nursery Plant and Fertilizer (NPF) lnfonnational Web-Based System.